SISTEM INFORMASI KELUAR MASUK BARANG DI KANTOR CABANG PT. RODA HAMMERINDO JAYA BERBASIS WEB - Novita Puspitasari; Eko Purwanto; Ery Permana Yudha (Jurnal DutaCom, 2023)
Roda Hammerindo Jaya is a company engaged in the distribution of caster wheels, material handling and hospital bed equipment. The process of entering and leaving goods is a company asset that greatly affects the smooth running of the company's business. So far, when the goods management process is still using a manual system, including recording incoming and outgoing goods based on travel documents and then copying them to a computer (spreadsheets). Because the data has not been computerized properly, so that from this process it sometimes causes errors in calculating goods, it is found that several items have a difference in the amount when calculating the stock and when information is needed about the stock of goods, the existing data is not necessarily valid with the existing goods. In this study the authors used the PIECES method to analyze system weaknesses and the Waterfall method for system development, using the PHP and MySQL programming languages as the database. For testing the system using the Blackbox Testing method. This research resulted in an information system for goods in and out at the branch office of PT. Roda Hammerindo Jaya is a web-based tool that makes it easy for users to manage stock and stock information and can print reports when needed. The test results that have been carried out using blackbox testing indicate that the system can run and function properly as expected.